The Implications of Air Humidity on Determining the Sun's Dip for the Start of Isha Prayer - Kurlian Puspa Dwi Dharma Yanti; Ahmad Adib Rofiuddin; Ahmad Abdillah Rauf Syam (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2026)
This study aims to explain the implications of air humidity on determining the beginning of Isha prayer time. This is because of the different times of Syafaq's disappearance at the same location, due to air humidity, which has led to differences of opinion regarding the dip of the Sun. This research is a qualitative study using a field research approach. The primary source is data collected through direct observation with a Sky Quality Meter (SQM) over 30 days in the highlands of Tanjung Heran Village and at Cemara Indah Beach. This study found that air humidity on the coast of Cemara Indah, with a value of <80%, detected the disappearance of Syafaq Ahmar at Dip -18°, which is the same as the dip of the Sun according to the Indonesian Ministry of Religious Affairs. Meanwhile, air humidity of 81-90% resulted in a variable dip in the Sun and, of course, Syafaq disappeared more quickly. In the highlands of Tanjung Heran Village, the air humidity of 95-99% caused Syafaq to be detected as disappearing faster than -18 °, with higher values indicating faster disappearance. Therefore, humidity levels are one of the factors that influence the calculation of the Sun’s Dip to determine the start time of the Isha prayer.